Procedures for Admitting Confessional Statements under the Evidence Act, 2011, Administration of Criminal Justice Act 2015 and the Administration of Criminal Justice Laws of Various States: Inconsistent or Complimentary? - Ogunmodede, Omotan Olusola (ABUAD Law Journal, 2023)
Confessional statements are very vital in Nigeria’s administration of criminal justice as many convictions are based on confessional statements. The major laws regulating the admissibility of confessional statements in Nigeria are Evidence Act 2011, Administration of Criminal Justice Act 2015 and Administration of Criminal Justice Laws of various States. The provisions of these laws seem to be inconsistent and create confusion on the admissibility of confessional statements. This paper defines and examines confessional statements under the Evidence Act 2011, the Administration of Criminal Justice Act 2015 and the Administration of Criminal Justice Laws of Various States. The paper examines various court decisions on the “conflicts” between the Evidence Act 2011, the Administration of Criminal Justice Act 2015 and the Administration of Criminal Justice Laws. The paper finds that the Evidence Act solely determines the admissibility of confessional statements while the Administration of Criminal Justice Act 2015 and the Administration of Criminal Justice Laws in conjunction with other evidence determines the weight to be attached to a confessional statement. The paper concludes that the Evidence Act and Administration of Criminal Justice Act 2015/ the Administration of Criminal Justice Law are therefore complementary rather than inconsistent.